2003
DOI: 10.1152/ajpregu.00442.2002
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids stimulate colonic transit via intraluminal 5-HT release in rats

Abstract: We studied whether physiological concentration of short-chain fatty acids (SCFAs) affects colonic transit and colonic motility in conscious rats. Intraluminal administration of SCFAs (100-200 mM) into the proximal colon significantly accelerated colonic transit. The stimulatory effect of SCFAs on colonic transit was abolished by perivagal capsaicin treatment, atropine, hexamethonium, and vagotomy, but not by guanethidine. The stimulatory effect of SCFAs on colonic transit was also abolished by intraluminal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
314
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(340 citation statements)
references
References 32 publications
(44 reference statements)
19
314
2
5
Order By: Relevance
“…Further, sodium butyrate has the ability to increase the gastric emptying and intestinal motility thereby increasing feed intake (Malbert et al, 1994). In addition to that butyrate and propionate induced phasic and tonic contraction in colonic circular muscle (Mitsui et al, 2005;Tazoe et al, 2008) also butyrate has been reported to induce enhancement of colonic motility via the release of 5-HT (Fukumoto et al, 2003).…”
Section: Feed Consumptionmentioning
confidence: 92%
“…Further, sodium butyrate has the ability to increase the gastric emptying and intestinal motility thereby increasing feed intake (Malbert et al, 1994). In addition to that butyrate and propionate induced phasic and tonic contraction in colonic circular muscle (Mitsui et al, 2005;Tazoe et al, 2008) also butyrate has been reported to induce enhancement of colonic motility via the release of 5-HT (Fukumoto et al, 2003).…”
Section: Feed Consumptionmentioning
confidence: 92%
“…Previous physiological studies reported the SCFAsinduced 5-hydroxytryptamine (5-HT) and PYY release (8,19). Thus, we performed double-staining for FFA2 and 5-HT, and FFA2 and PYY.…”
Section: Tissue Distribution Of Free Fatty Acid Receptor 2 and 3 (Ffamentioning
confidence: 99%
“…Therefore, propionate-induced circular muscle contractions might be involved in FFA3. SCFAs have been reported to enhance colonic motility via the release of 5-HT (19,38). There are two possible source of 5-HT for the propionate-induced circular muscle contraction: enteroendocrine cells that are numerous throughout the gastrointestinal tract (16), and 5-HT containing mast cells that occur in the mucosal lamina propria of the rat intestine (69).…”
Section: Circular Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Sua liberação para o lúmen ou lâmina própria faz com que atue sobre células entéricas do sistema nervoso e inicie atividades secretó-rias e crescimento celular de vários tecidos, incluindo vilosidades e criptas intestinais (Fukumoto et al 2003, Hasler 2009, Khan & Ghia 2010.…”
Section: Introductionunclassified